Pendidikan Karakter Nasionalisme Melalui Mars Syubbanil Muslimin Dan Tembang Syair Di Pesantren Al-Khairiyah - Rahayu Permana (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2022)
This research departs from a local study about instilling the character of nationalism in the Al-Khairiyah Islamic boarding school which was founded in 1925 by a great ulama figure from Banten, namely Brigadier General KH. Syamun is a national hero. It is very interesting when in Al-Khairiyah Islamic boarding school in terms of character value education because education in Islamic boarding schools requires character education content. However, what is studied here is only on nationalism character education. The method to study this research is a naturalistic qualitative method with a historical research approach. While the research results obtained are that the boarding school is cared for and guided by KH. Syam'un tries to instill the importance of the character of nationalism in his students so that they continue to love their homeland. Nationalism character education can be seen through every lesson that will be started, the students must sing the Muslim subanil march and rhyme songs systematically. With the habit of continuing to sing Muslim subanil marches and poetry songs, the results of character education have been seen, namely after the independence of the Republic of Indonesia was proclaimed, many Al-Khairiyah students were involved in efforts to maintain the independence and independence of the nation.